1986
DOI: 10.1289/ehp.8665343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of di(2-ethylhexyl) phthalate on the gonadal pathophysiology, sperm morphology, and reproductive performance of male rats.

Abstract: Dietary exposure of adult male F344 rats to 0, 320, 1250, 5000, or 20,000 ppm DEHP for 60 consecutive days resulted in a dose-dependent reduction in total body, testis, epididymis, and prostate weights at 5000 and 20,000 ppm. Degenerative changes were observed in testis, along with decreased testicular zinc content, reduced epididymal sperm density and motility, and increased occurrence of abnormal sperm at 20,000 ppm. There was a trend towards reduced testosterone and increased luteinizing hormone and follicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…This finding is consistent with previous reports that perinatal exposure of male rats to DEHP produces adverse effects in androgenresponsive tissues [32]. Specifically, 2,000 mg/kg/ day DEHP has been previously shown to cause testicular atrophy [24], damage to the seminiferous epithelium [33] and reduced epididymal sperm density and motility [34] in rats.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous reports that perinatal exposure of male rats to DEHP produces adverse effects in androgenresponsive tissues [32]. Specifically, 2,000 mg/kg/ day DEHP has been previously shown to cause testicular atrophy [24], damage to the seminiferous epithelium [33] and reduced epididymal sperm density and motility [34] in rats.…”
Section: Discussionsupporting
confidence: 93%
“…It also reduces testicular T production in vivo and T levels in the testis [21]. Other studies have reported that exposure of rats to DEHP (200 mg/kg/day) causes various effects, including a 77% decrease in the activity of the steroidogenesis enzyme 17β-hydroxysteroid dehydrogenase, a 50% reduction in T production in Leydig cells [22], enhanced testosterone 5α-reductase (T5α-R) activity in the testis [23], and reduced epididymal sperm density and motility [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that mean DEHP intake is 8.2 µg/kg body weight per day for adults 3) . During recent years, DEHP has been Dietary exposure of adult male rats given 0, 320, 1,250, 5,000, and 20,000 ppm DEHP (equivalent to 0, 17.5, 69.2, 284.1 and 1156.4 mg/kg/day, respectively) for 60 days, when mated with untreated adult females, did not affect the rate of neonatal death, initial pup weight or growth (up to PND 7), whereas the average litter size decreased in rats fed 20,000 ppm DEHP 13) . Inhalation exposure of adult male Wistar rats to 25 mg/m 3 for 6 h/day for 8 wk increased plasma testosterone level and seminal vesicle weight in a dosedependent manner 14) .…”
Section: Introductionmentioning
confidence: 92%